1)2аа+а*3а+а²2)2х²*3ху-4х*5х²у3)у²*2х-3х²*2у+2ху*2у-ху*(-4х)4)хх*(-2х)-у*3ху+7х²*(-2х)-4у²*2хупростите выражение
1)2аа+а*3а+а²
2)2х²*3ху-4х*5х²у
3)у²*2х-3х²*2у+2ху*2у-ху*(-4х)
4)хх*(-2х)-у*3ху+7х²*(-2х)-4у²*2х
упростите выражение
Ответ(ы) на вопрос:
[latex]2aa+a*3a+a^2=2a^2+3a^2+a^2=6a^2 \\ \\ 2x^2*3xy-4x*5x^2y=6x^3y-20x^3y=-14x^3y \\ \\ y^2*2x-3x^2*2y+2xy*2y-xy*(-4x)= \\ 2y^2x-6x^2y+4y^2x+4x^2y=6y^2x-2x^2y \\ \\ xx*(-2x)-y*3xy+7x^2*(-2x)-4y^2*2x= \\ -2x^3-3xy^2-14x^3-8y^2x=-16x^3-11y^2x[/latex]
Не нашли ответ?
Похожие вопросы